Structure and magnetism of (La/Sr)2M0.5IrV0.5O4 and topochemically reduced (La/Sr)2M0.5IrII0.5O3 (M = Fe, Co) complex oxides - Page, J; Hayward, M (American Chemical Society, 2019)
Neutron powder diffraction data show that Sr2Fe0.5Ir0.5O4, Sr2Co0.5Ir0.5O4, and La0.5Sr1.5Co0.5Ir0.5O4 all adopt undistorted, n = 1 Ruddlesden-Popper structures in which the Ir5+ and Fe3+/Co3+/Co2+ cations are statistically disordered over all the octahedral coordination sites. Magnetization data indicate the two cobalt phases are spin glasses at low temperature, while Sr2Fe0.5Ir0.5O4 appears to adopt an antiferromagnetic state with very small magnetically ordered domains. Topochemical reduction with a Zr getter converts the tetragonal A2M0.5Ir0.5O4 phases to the corresponding orthorhombic A2M0.5Ir0.5O3 phases in which the Ir2+ and Fe2+/Co2+/Co1+ cations are located in approximately square-planar coordination sites. Magnetization data indicate Sr2Fe0.5Ir0.5O3 is a spin glass below TG ∼ 30 K, while Sr2Co0.5Ir0.5O3 appears to be antiferromagnetic below TN ∼ 25 K and La0.5Sr1.5Co0.5Ir0.5O3 shows no sign of magnetic order for T > 5 K. The magnetic behavior of both the A2M0.5Ir0.5O4 and A2M0.5Ir0.5O3 phases is discussed on the basis of metal d-electron count and structural features.